Investment model of marital commitment among married postgraduate students in Tehran, Iran - Seyedsalehi, Shideh (2021)
Family is not only the place to meet the emotional, material, evolutionary and spiritual needs of its own members, but it is also the origin of human emotions and the main focus of the most traditional intimate relationships and interpersonal interactions, including marriage. A marital relationship has always been an emphasized area. It also has been closely related to commitment as one of the key role players in either the success or the failure of marriages. Rusbult's Investment Model emphasized that increasing in satisfaction level, decreasing in the level of the quality of alternatives, and increasing in investment size would strengthen individuals' marital commitment, and it can contribute to marital stability. This study used Rusbult's Investment Model to investigate the relationship between marital satisfaction, the quality of alternatives, investment size, and marital commitment due to the increase in the rate of divorces in Iran over the last decade. The current cross-sectional study determined and evaluated the relationships between the satisfaction level, quality of alternatives, investment size, the demographic factors with the marital commitment, and finding the predictors of marital commitment among the married individual postgraduate students in Iran. Based on the convenience sampling method, 473 respondents have been chosen to cover the aim of the study. The Farsi translated version of a standard self-administrated Web-based questionnaire was adopted. The reliability of the questionnaire was tested by Cronbach's alpha in both pilot and the actual study. All Cronbach's Alphas were above 0.80; therefore, all subscales were reliable. Accordingly, the findings of the study revealed significant bivariate correlations between satisfaction level, quality of alternatives, investment size, gender and having children with marital commitment; also, no significant correlation has been found between age, marital duration, family income and spouse's educational level with marital commitment. among respondents. Moreover, Bootstrap multiple linear regression on the relevant variables revealed gender as the strongest predictor of marital commitment, followed by marital satisfaction, the quality of alternatives and the investment size among respondents. The predictor model explained 59.5 percent of the variance in respondents' marital commitment in the study. Therefore, the results lend support to the use of Rusbult's Investment Model that explains significant factors that increase an individuals' marital commitment in the context of Iran society. This study shed light on the stability of marriage's contributors to help the policymakers and professionals to provide more efficient policies and programs. Further studies on Rusbult's Investment Model might assist in generalizing findings for greater benefit.